Clinical experience for modified thoracoabdominal nerve block through perichondrial approach (M-TAPA) in five patients. dermatomal evaluation and application of different volumes: A case series and review of literature - Çiftçi, Bahadır; Güngör, Hande; Alver, Selçuk; Akın, Ayşe Nurmen; Özdenkaya, Yaşar; Tulgar, Serkan (AVES, 2023)
Thoracoabdominal nerves block through perichondrial approach (TAPA) is a novel block and provides abdominal analgesia. TAPA block targets the both anterior and the lateral branches of the thoracoabdominal nerves. Modified-TAPA (M-TAPA) was defined due to the need for blocking certain dermatomes depending on the surgical incision sites. In the literature, the knowledge about the efficiency and dermatomal coverage of M-TAPA is limited. In this case series, we want to report our experiences with this issue.
Keywords: Abdominal Surgery; Dermatomal Coverage; Modified Thoracoabdominal Nerves Block; Postoperative Analgesia; Regional Anaesthesia